1979
DOI: 10.1073/pnas.76.4.1819
|View full text |Cite
|
Sign up to set email alerts
|

Selective growth of some rodent epithelial cells in a medium containing citrulline.

Abstract: We have defined a medium (called Sun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Day-12 and -34 cells, on the other hand, not only formed monolayers but also exhibited significant trans -differentiation into fibroblast-like mesenchymal cells within 6–12 days post plating (Figure 2b). These changes were not driven by contamination from the mesenchymal cells during the isolation process, as the purified crypts (Supplementary Figures 1D and E) were negative for α-smooth muscle actin expression either in uninfected or in 6–34-day post-infected crypt cellular extracts (Supplementary Figure 1F), whereas cells isolated from uninfected mouse distal colon not only failed to grow beyond 1–2 weeks in culture conditions that included D-valine 40 or citrulline, 41 but never changed their phenotype (data not shown). When the cells in monolayers were stained for markers of EMT, they stained positive for vimentin but negative for E-cadherin, suggesting an EMT-like process in vitro (Figure 2d).…”
Section: Resultsmentioning
confidence: 98%
“…Day-12 and -34 cells, on the other hand, not only formed monolayers but also exhibited significant trans -differentiation into fibroblast-like mesenchymal cells within 6–12 days post plating (Figure 2b). These changes were not driven by contamination from the mesenchymal cells during the isolation process, as the purified crypts (Supplementary Figures 1D and E) were negative for α-smooth muscle actin expression either in uninfected or in 6–34-day post-infected crypt cellular extracts (Supplementary Figure 1F), whereas cells isolated from uninfected mouse distal colon not only failed to grow beyond 1–2 weeks in culture conditions that included D-valine 40 or citrulline, 41 but never changed their phenotype (data not shown). When the cells in monolayers were stained for markers of EMT, they stained positive for vimentin but negative for E-cadherin, suggesting an EMT-like process in vitro (Figure 2d).…”
Section: Resultsmentioning
confidence: 98%
“…This finding did not receive the recognition it may have deserved as it was widely known that most mammalian cells do not require arginine for growth in tissue culture because media that contain citrulline in place of arginine can most often support normal growth. 6,10 In 1979, Sun et al 19 demonstrated definitively that some tumor cells are unable to utilize citrulline for growth. However, most of these investigators concluded that Mycoplasma contamination of tissue culture should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous but inconclusive attempts to solve this problem by the use of selective media that inhibit fibroblast growth . These include media in which L-valine is replaced by D-valine (4), media in which arginine is replaced by citrulline (21), and media lacking tyrosine (2) proach to overcoming the problem of fibroblast overgrowth . Although colostrum, in the absence of serum, supports the growth of such epithelial cells as the MDCK cell line, milk obtained as early as a week after the birth of a calf is completely inactive.…”
Section: Discussionmentioning
confidence: 99%